Morita–Baylis–Hillman reaction in eutectic solvent under aqueous medium. Issue 67 (30th June 2016) - Zhao, Sanhu; Zhi, Hangyu; Zhang, Mi; Yan, Qin; Fan, Jianfeng; Guo, Jinchang
Abstract : Aqueous solvent-catalyst system formed by DES (1ChCl/2Gly) and DABCO is more useful and practical to the Morita–Baylis–Hillman reaction. Abstract : A series of deep eutectic solvents (DESs) based on choline chloride were prepared and used in the Morita–Baylis–Hillman (M–B–H) reaction. Research showed that the composite solvent (1ChCl/2Gly DES–H2 O) is a very effective solvent media for all substrates tested. Under the mild reaction conditions, DABCO catalyzed M–B–H reactions proceed very quickly and efficiently. It is particularly important that the solid M–B–H adducts suspended in the reaction system at the end of the reaction, which can be obtained by simple filtering. Such simple product processing is not reported in the previous literature. The composite solvent (1ChCl/2Gly DES–H2 O) was reused directly without any activation process. After six cycles, the yields almost remained unchanged. This protocol has notable advantages such as low cost, ease of work-up and reuse of DES conveniently, which could contribute to the development of new solvent system for use in continuous chemical processes.